Wild birds and mammals used by villagers from Lower Urubamba River at Cusco, Peru - Costa, Juan F. (2018)
Birds and mammals are the most important resource of protein for original groups of the amazon rainforest. Most of the meat is used for food and other parts of the animals are designates for the production of handicrafts, ornaments and other daily objects. Considering the use and exploitation of the fauna, the objectives of this study were: a) to identify the species of birds and mammals used by the local population; b) to determine what the uses of this animal are, and c) to calculate the economic value of the biomass extracted. We registered the exploitation and use of the species through surveys between the families. All the information was recorded, analyzed and systematized. We found that in the Lower Urubamba River, local families use 10 species of birds and 12 species of mammals. Paujil (Mitu tuberosum), Tinammus (Crypturellus sp. and Tinamus tao) are the species more commonly used. The lowland pacca (Cuniculus paca), Red brocket deer (Mazama americana) and tapir (Tapirus terrestris) are the mammals with the more extracted biomass. The most important use of these animals is for food (as meat) for subsistence of the families.